Process for lining the inner wall of a dryer cone

CN122918567APending Publication Date: 2026-10-16CHANGZHOU LIJUN DRYING ENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611225671.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

传统搪瓷工艺长期受困于技术短板,难以满足这类高端生产场景的需求,逐渐暴露出更多的技术缺陷

Benefits of technology

[0012] (1) Significant improvement in uniformity of ceramic layer thickness - Through precise control of spraying parameters, uniform deposition of glaze powder on the inner wall of the cone is ensured. The optimized glaze formula has a fluidity in the molten state that is more suitable for the cone structure and can be evenly spread on the cone wall, avoiding the defects of local glaze layers being too thin or too thick.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of industrial equipment surface treatment, and particularly relates to a dry machine cone inner wall enamel process, comprising the following steps: S1, base surface treatment: mechanically removing rust on the cone inner wall, then roughening the inner wall, controlling the inner wall roughness in the interval range of 5-15 mu m, then cleaning the inner wall to remove residual iron filings, dust, oil stains and other impurities, and thoroughly drying after cleaning to avoid secondary oxidation of the base surface, compared with the prior art, the present application improves the uniformity of the porcelain layer thickness, and improves the bonding strength of the porcelain layer and its thermal shock stability and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of surface treatment technology for industrial equipment, and more particularly to an enamel enamel process for the inner wall of a dryer cone. Background Technology

[0002] In the pharmaceutical, chemical, and food industries, the double-cone rotary vacuum dryer is a core piece of equipment for processing heat-sensitive, easily oxidized, and corrosive materials. The inner wall of the cone is the critical area in direct contact with the material, and its surface properties directly determine the overall lifespan of the machine, the drying quality of the material, and production safety. Currently, the mainstream practice in the industry is to coat the inner wall of the cone with an enamel (also known as glass enamel) layer. This solution essentially involves high-temperature sintering of a high-silicon, corrosion-resistant glass enamel glaze onto the surface of a carbon steel substrate, allowing the glaze layer to firmly bond with the metal substrate, forming a smooth, dense, and chemically inert protective layer. This layer not only isolates the metal substrate from corrosive materials but also prevents metal ion contamination, while simultaneously meeting the requirements of some industries for easy cleaning of the inner wall.

[0003] However, with the upgrading of processes in the pharmaceutical and chemical industries, the operating conditions for material drying are becoming increasingly stringent. Some chemical intermediates and acidic crystalline materials are not only highly corrosive but also generate localized friction on the inner wall of the cone. The combined effect of the vacuum state during equipment operation and the rotation of the cylinder places even higher demands on the adhesion, thermal shock resistance, and wear resistance of the enamel layer. Traditional enamel processes have long been hampered by technological shortcomings, making it difficult to meet the needs of such high-end production scenarios and gradually exposing more technical deficiencies.

[0004] Therefore, there is an urgent need to develop an enamel process suitable for the inner wall of the dryer cone to solve the above-mentioned technical performance problems. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of existing technologies by proposing a process for enamel lining the inner wall of a dryer cone.

[0006] A process for enamel lining the inner wall of a dryer cone includes the following steps:

[0007] S1. Surface treatment of the substrate: Mechanically remove rust from the inner wall of the cone, then roughen the inner wall to control the roughness within the range of 5-15μm. Then clean the inner wall to remove residual iron filings, dust, oil and other impurities. After cleaning, dry thoroughly to avoid secondary oxidation of the substrate surface.

[0008] S2. Electrostatic dry spraying: The electrostatic dry spraying process is used to sequentially spray the base glaze, transition layer and top glaze on the inner wall of the treated cone. The dry film thickness of the base glaze, transition layer and top glaze are controlled differently according to different positions of the cone. The median particle size of the glaze powder of the base glaze, transition layer and top glaze is controlled in the range of 20-40μm, and the moisture content is strictly controlled below 0.1wt%.

[0009] S3. Sintering process: The cone after spraying is placed in a controlled atmosphere electric furnace for sintering. During the heating stage of the sintering process, the heating rate in the furnace is strictly controlled within the range of 3-5℃ / min, the maximum sintering temperature is controlled between 780-800℃, the holding time is controlled between 10-15 minutes, and the cooling rate in the furnace is strictly controlled within the range of 2-4℃ / min.

[0010] S4. Post-processing: After sintering, allow the enamel layer to cool naturally to room temperature and clean the surface.

[0011] The beneficial effects of this invention are:

[0012] (1) Significant improvement in uniformity of ceramic layer thickness - Through precise control of spraying parameters, uniform deposition of glaze powder on the inner wall of the cone is ensured. The optimized glaze formula has a fluidity in the molten state that is more suitable for the cone structure and can be evenly spread on the cone wall, avoiding the defects of local glaze layers being too thin or too thick.

[0013] (2) Significant improvement in bonding strength - The rare earth lanthanum ions of modified manganese oxide can precisely control the high-temperature diffusion rate of manganese ions, avoid the excessive enrichment or insufficient diffusion of manganese ions, promote the formation of a more continuous metallurgical interface with higher lattice matching degree in the cobalt, nickel, manganese and copper multi-element spinel transition layer, refine the spinel grains, eliminate the micro-pores of the interface, and effectively improve the bonding strength of the ceramic layer.

[0014] (3) Significant improvement in thermal shock resistance and wear resistance – Through the gradient transition of thermal expansion coefficients of base glaze, transition layer and top glaze, the interfacial stress between coatings is significantly reduced. At the same time, the modified silicon carbide component introduced into the glaze formula achieves chemical bonding between silicon carbide and enamel system by constructing Si-O-Ti covalent bonds. Through rare earth grain refinement and matching thermal expansion gradient, the residual stress of the coating is greatly reduced, the structural strength of the glaze layer is significantly improved, and the risk of crack propagation caused by thermal stress is reduced. This effectively reduces the wear rate of the glaze layer and improves the thermal shock resistance of the glaze layer. Detailed Implementation

[0015] The present invention will be further explained below with reference to specific embodiments.

[0016] The glaze formulation of this invention reduces the interfacial stress of the coating by matching the gradient thermal expansion coefficients of the base glaze, transition layer, and top glaze. At the same time, through the synergistic effect of functional components, it specifically improves the core properties of the enamel layer, such as bonding strength, impact resistance, wear resistance, and thermal shock resistance.

[0017] I. The specific formula design concept for the glaze is as follows:

[0018] Base glaze: By weight, the components are: 30-35 parts silicon dioxide, 15-20 parts boron trioxide, 4-6 parts aluminum oxide, 10-15 parts titanium dioxide, 2-4 parts cobalt oxide, 3-5 parts nickel oxide, 1-3 parts copper oxide, 3-6 parts potassium oxide, 5-8 parts sodium oxide, 2-4 parts sodium fluorosilicate, 2-5 parts sodium nitrate, 2-3 parts nano zirconium oxide, and 1-2 parts modified manganese oxide.

[0019] The formulation of this base glaze is designed to achieve a high degree of matching with the thermal expansion coefficient of the carbon steel matrix by adjusting the relative content of the adhesive and glass phase forming components, while ensuring sufficient melting and spreading during sintering to form a strong bonding interface.

[0020] The specific raw material ratio for modified manganese oxide is as follows:

[0021] Based on 100 parts of industrial manganese oxide powder (purity ≥99%, 200 mesh), the modified system formulation is as follows:

[0022] ①Silane coupling agent KH-550: 2.0-2.5 parts (organic coating modification to improve powder dispersibility and glass phase compatibility) – 2.3 parts were weighed out during preparation.

[0023] ②Nano-lanthanum oxide: 0.8-1.2 parts (rare earth modifier, inorganic doping modification, stabilizes manganese valence state, regulates diffusion rate) – 1.0 part is weighed out during preparation.

[0024] ③ Anhydrous ethanol: 40-50 parts (dispersing solvent) — 45 parts are weighed out during preparation.

[0025] ④ Deionized water: 5-8 parts (hydrolysis aid) – 6.5 parts are weighed out during preparation.

[0026] ⑤ Glacial acetic acid: 0.3-0.5 parts (pH adjuster, to regulate the hydrolysis rate of silane) – 0.4 parts are weighed out during preparation.

[0027] The preparation process of modified manganese oxide is as follows:

[0028] Step 1: Solvent system preparation

[0029] Mix anhydrous ethanol and deionized water according to the specified ratio, add glacial acetic acid to adjust the pH of the system to 4.5-5.0, stir at low speed for 5 minutes to form a uniform weakly acidic hydrolysis solvent system.

[0030] Step 2: Silane hydrolysis activation

[0031] The weighed KH-550 silane coupling agent was slowly added dropwise to the above solvent system. The mixture was kept at a constant temperature of 55℃ and a speed of 300r / min for 30min to allow the silane to be fully hydrolyzed to generate active silanol groups.

[0032] Step 3: Rare earth doping modification

[0033] Manganese oxide powder and nano-lanthanum oxide powder were added sequentially to the activated silane system, the stirring speed was increased to 500 r / min, and the mixture was stirred continuously at a constant temperature of 55-60℃ for 90-120 min.

[0034] Step 4: Let it sit and mature.

[0035] Stop stirring and let it stand at room temperature for 40 minutes to allow the modified groups to fully bond and solidify, eliminate free active groups on the powder surface, and improve the stability of the modified layer.

[0036] Step 5: Post-processing

[0037] The matured slurry is spread evenly on a tray with a thickness of 8-10 mm, and then placed in a constant temperature oven at 110-120℃ for 2.5-3 hours to completely remove the solvent and solidify the modified layer. After drying, it is pulverized using an air jet mill and passed through a 300-mesh standard sieve to finally obtain powdered modified manganese oxide, which is then sealed for later use.

[0038] Conventional unmodified manganese oxide has two major common defects in the industry: First, the powder has strong agglomeration and uneven dispersion in the borosilicate glass phase of the base glaze, resulting in uneven density of local spinel phase formation and poor stability of glaze bonding strength; Second, the diffusion rate of manganese ions is too fast during high-temperature sintering, which easily leads to manganese enrichment at the interface, color bleeding on the surface of the glaze, and local microcrack defects. At the same time, the manganese valence state is prone to fluctuation, affecting the continuity of the multi-element spinel transition layer.

[0039] Modified manganese oxide adopts a silane-lanthanum oxide rare earth composite modification process to achieve dual modification and enhancement through "organic coating + inorganic doping": ① The silane coupling agent forms a uniform organic coating layer on the powder surface, solving the problem of powder agglomeration and improving the compatibility with the borosilicate glass phase; ② Rare earth lanthanum oxide ions are doped into the interstices of the powder lattice, precisely locking the valence state of manganese ions and controlling the high-temperature diffusion rate, so that manganese oxide is upgraded from an ordinary filler to a controllable interface bonding stabilizer + spinel phase refiner, solving the interface defects of traditional base glaze from the root of the powder.

[0040] Transition layer: By mass, the components are: 35-40 parts silicon dioxide, 12-18 parts boron trioxide, 6-8 parts aluminum oxide, 15-20 parts titanium dioxide, 1-2 parts cobalt oxide, 2-3 parts nickel oxide, 1-2 parts copper oxide, 4-7 parts potassium oxide, 6-9 parts sodium oxide, 2-3 parts sodium fluorosilicate, 2-4 parts sodium nitrate, 3-5 parts nano-zirconium oxide, and 2-3 parts modified silicon carbide.

[0041] The formulation design of this transition layer is achieved by adjusting the relative contents of silica, boron trioxide, and alkali metal oxides to gradually transition the coefficient of thermal expansion from the range of the base glaze to the range of the top glaze, while improving the toughness of the transition layer and buffering the mechanical stress transmitted from the cone substrate.

[0042] The specific raw material ratio for modified silicon carbide is as follows:

[0043] Based on 100 parts of nano-silicon carbide powder (purity ≥99.5%, 600 mesh), the formulation of the composite modification system is as follows:

[0044] ① Tetrabutyl titanate: 3.0-3.5 parts (titanium sol precursor, inorganic grafting modification, constructing Si-O-Ti bonds, enhancing interfacial compatibility) – 3.3 parts were weighed out during preparation.

[0045] ②Nano-lanthanum oxide: 0.6-1.0 parts (rare earth modifier, refines grains, eliminates interface defects, and stabilizes interface structure) – 0.8 parts are weighed out during preparation.

[0046] ③ Anhydrous ethanol: 45-55 parts (dispersing solvent) — 50 parts are weighed out during preparation.

[0047] ④ Deionized water: 6-9 parts (hydrolysis initiator) – 7.5 parts are weighed out during preparation.

[0048] ⑤ Glacial acetic acid: 0.4-0.6 parts (pH buffer, to regulate the slow hydrolysis of titanium sol) – Weigh out 0.5 parts during preparation.

[0049] The preparation process of modified silicon carbide is as follows:

[0050] Step 1: Preparation of buffer hydrolysis solvent

[0051] Mix anhydrous ethanol and deionized water according to the specified ratio, add glacial acetic acid to adjust the pH of the system to 4.2-4.8, stir at low speed at room temperature for 6 minutes to form a weakly acidic and stable buffer system.

[0052] Step 2: Preparation of active titanium sol

[0053] Tetrabutyl titanate was slowly added dropwise to a buffer solvent, and stirred at a constant temperature of 60℃ and a uniform speed of 350r / min for 25min to prepare a uniform and transparent active titanium sol.

[0054] Step 3: Rare Earth Composite Modification

[0055] Add silicon carbide powder and nano lanthanum oxide powder in sequence, increase the stirring speed to 550 r / min, and stir continuously at a constant temperature of 60-65℃ for 100-120 min;

[0056] Step 4: Let it mature at room temperature

[0057] Stop stirring and let it stand at room temperature in a sealed container for 50 minutes to allow the titanium sol to fully condense and solidify, stabilize the lanthanum oxide ions, completely eliminate free active groups on the powder surface, prevent the modified components from decomposing and falling off during high-temperature sintering, and ensure the high-temperature stability of the modified layer.

[0058] Step 5: Drying, curing, crushing and sieving

[0059] The modified slurry is spread into a thin layer of 7-9 mm and dried at a constant temperature of 115-125℃ for 3.0 h to completely remove the solvent and solidify the composite modified layer. After air jet milling, it is passed through an 800-mesh standard sieve to obtain powdered modified silicon carbide, which is then sealed and dried for storage.

[0060] Conventional unmodified silicon carbide has three major technical shortcomings that restrict the overall performance of the enamel coating on the dryer cone: First, the surface of silicon carbide powder is extremely inert, resulting in poor compatibility with the glass phase of the silicon boron base glaze and the cobalt-nickel-manganese-copper spinel transition layer. The powder is prone to floating and agglomeration, and the interface is prone to micropores and delamination defects. Second, the thermal expansion coefficient of silicon carbide is not well matched with the carbon steel matrix and the enamel coating. Under the alternating hot and cold conditions of the equipment, residual stress at the interface is prone to occur, inducing the propagation of microcracks. Third, ordinary silicon carbide only has a single reinforcing effect and cannot participate in the metallurgical bonding of the interface, making it difficult to synergistically optimize the density and corrosion resistance of the transition layer.

[0061] The modified silicon carbide is modified using a titanium sol-lanthanum oxide composite surface modification process. The active titanium sol generated by the hydrolysis of tetrabutyl titanate forms a uniform TiO2 active coating layer on the silicon carbide surface, constructing stable Si-O-Ti covalent bonds and completely breaking the surface inertness of silicon carbide. Trace amounts of rare earth lanthanum oxide doping refine the surface grains, passivate interface defects, and stabilize the high-temperature microstructure, upgrading silicon carbide from a traditional "inert filler aggregate" into a gradient functional reinforcing phase that can bond, toughen, and relieve stress, forming a highly efficient synergistic reinforcement system with the modified manganese oxide spinel interface.

[0062] Glaze: By weight, the components are: 40-45 parts silicon dioxide, 10-15 parts boron trioxide, 8-10 parts aluminum oxide, 20-25 parts titanium dioxide, 2-3 parts copper oxide, 5-8 parts potassium oxide, 8-10 parts sodium oxide, 1-3 parts sodium fluorosilicate, 1-3 parts sodium nitrate, 5-8 parts nano zirconium oxide, 3-5 parts silicon carbide, 0.2-1 parts borax, and 0.5-1 parts bentonite.

[0063] The formulation of this glaze is designed to significantly improve the chemical stability, wear resistance, and impact resistance of the glaze layer by increasing the content of glass phase forming components and nano-reinforced hard phase components, while ensuring the high gloss of the glaze layer and preventing material from sticking to the wall.

[0064] The preparation processes for the base glaze, transition layer, and top glaze described above are entirely the same, and the specific steps are as follows:

[0065] All accurately weighed raw materials are placed in a dedicated mixer for thorough mixing to obtain a homogeneous batch. The batch is then placed in a dedicated frit furnace for high-temperature melting, with the melting temperature controlled between 1200-1300℃ to ensure complete melting and reaction. The molten glaze is then quenched in cold water to form loose, porous glaze blocks. These blocks are then placed in a ball mill with appropriate auxiliary materials for wet ball milling until the median particle size of the glaze powder reaches the range of 20-40μm. After ball milling, the glaze powder is dried in a dedicated drying device, with the moisture content strictly controlled below 0.1wt%. After drying, the glaze powder is finely sieved to remove excessively large particles or impurities, ultimately obtaining glaze powder that meets the requirements.

[0066] II. The specific process steps for the inner wall of the dryer cone are as follows:

[0067] Step 1: Substrate Surface Treatment

[0068] First, the inner wall of the cone undergoes comprehensive mechanical rust removal using specialized wire wheels or sandblasting equipment to thoroughly remove oxide scale, rust, oil, and other impurities from the inner wall surface. The inner wall surface exhibits a completely uniform metallic luster, free of any residual oxide scale, rust, or oil residue. Subsequently, professional roughening equipment is used to uniformly roughen the inner wall, strictly controlling the roughness Ra of the cone's inner wall within the range of 5-15 μm. This roughness range ensures a uniform mechanical anchoring structure, enhancing the bonding strength between the glaze layer and the substrate, while avoiding excessive roughness leading to localized pinhole defects in the glaze layer, or insufficient roughness resulting in inadequate glaze adhesion area.

[0069] After the roughening treatment is completed, the inner wall of the cone is thoroughly cleaned with a metal cleaner to completely remove residual iron filings, dust, oil, and other impurities. The inner wall is then repeatedly rinsed with clean water to ensure all cleaning agent residue is completely removed. After cleaning, the inside of the cone is thoroughly dried with hot air to completely dry the moisture on the inner wall and prevent secondary oxidation of the substrate surface. After drying, a temporary protective layer is applied to the inner wall surface to prevent dust or impurities from re-contaminating the surface.

[0070] Step 2: Electrostatic dry spraying

[0071] An electrostatic dry spraying process is used to sequentially spray a base glaze, a transition layer, and a top glaze onto the inner wall of the treated cone. The dry film thickness of the base glaze, transition layer, and top glaze is differentiated according to different positions of the cone. The specific control parameters are as follows: the electrostatic voltage of the spray gun is stably controlled at 70-90kV (80kV in this example); the vertical distance between the spray gun and the inner wall of the cone is strictly controlled at 10-25cm (15cm in this example); and the rotation speed of the cone is precisely matched with the moving speed of the spray gun to ensure uniform deposition of glaze powder on the inner wall of the cone.

[0072] During spraying, a base coat is first evenly sprayed onto the inner wall of the cone. The dry film thickness of the base coat is controlled differently depending on the location of the cone: in stress concentration areas such as the large end, small end, and transition arc section of the cone, the dry film thickness of the base coat is controlled within the range of 100-150 μm; in the straight section of the cone, the dry film thickness is controlled within the range of 80-120 μm. After the base coat is applied, the cone is placed in a dedicated drying device and dried at 120-150℃ for 15-30 minutes (in this example, it is set to 130℃ for 20 minutes) to allow the moisture in the base coat to evaporate evenly. After drying, a transition layer is evenly sprayed onto the base coat. The dry film thickness of the transition layer is also controlled differently depending on the location of the cone: in stress concentration areas, the dry film thickness of the transition layer is controlled within the range of 50-80 μm; in the straight section, the dry film thickness is controlled within the range of 40-60 μm. After the transition layer is sprayed, the cone is placed in a dedicated drying device again and dried at 120-150℃ for 15-30 minutes (in this example, it is set to dry at 130℃ for 20 minutes) to allow the moisture in the transition layer to evaporate evenly.

[0073] After drying, a layer of top glaze is evenly sprayed onto the transition layer. The dry film thickness of the top glaze is also controlled differently depending on the location of the cone: in the stress concentration area, the dry film thickness of the top glaze is controlled in the range of 150-200μm; in the straight section area, the dry film thickness of the top glaze is controlled in the range of 120-180μm.

[0074] Step 3: Sintering process

[0075] After all the spraying processes are completed, the cone is placed in a dedicated controlled atmosphere electric furnace for one-time sintering. During the heating stage from room temperature to the maximum sintering temperature, the heating rate in the furnace needs to be strictly controlled within the range of 3-5℃ / min (4℃ / min in this example). This slow heating rate is to ensure the temperature uniformity of the entire cross-section of the cone and avoid excessive temperature difference inside the cone due to excessive heating rate, which could lead to thermal deformation or thermal stress concentration. At the same time, slow heating allows some components in the glaze to fully melt and react, avoiding unevenness, pinholes and other defects on the glaze surface due to delayed melting in some areas.

[0076] Based on the melting characteristics of the glaze formulation, the maximum sintering temperature range in this embodiment is set to 780-800℃. After the furnace temperature reaches the maximum sintering temperature, it is held within this temperature range for 10-15 minutes (in this embodiment, it is set to hold for 15 minutes at a maximum of 800℃). This holding time is designed based on the specifications and dimensions of the cone and the thickness of the glaze layer to ensure that the components in the glaze can fully complete the melting reaction and that the elements at the interface can fully diffuse and penetrate, thereby forming a strong spinel microcrystalline transition layer between the glaze layer and the substrate. At the same time, during the holding process, the glazes of different coatings can fully fuse to form a uniform overall coating structure.

[0077] After the heat preservation stage is completed, the cone is gradually cooled from the sintering temperature to room temperature. The cooling process needs to be carried out at a controllable rate of temperature change, and the cooling rate is strictly controlled within the range of 2-4℃ / min (3℃ / min in this example). This slow cooling rate is to avoid the generation of large thermal stress inside the cone due to the excessive cooling rate, which could lead to problems such as glaze cracking or substrate deformation exceeding the tolerance. At the same time, slow cooling can ensure that the enamel layer can fully release the interfacial stress caused by the difference in thermal expansion coefficients during the cooling process, further improving the structural stability of the coating.

[0078] Step 4: Follow-up processing

[0079] After the sintering process is completed, the cone is allowed to cool naturally to room temperature in the electric furnace. Then, the cone is removed from the electric furnace, and the surface of the enamel layer is thoroughly cleaned. Clean compressed air is used to blow away dust or a small amount of molten residue on the surface, ensuring the cleanliness of the enamel layer surface. After all the testing processes are completed and passed, the inner wall of the cone is properly protected in a dry and dust-free environment to avoid damage or secondary contamination to the enamel layer during subsequent installation or storage.

[0080] The following embodiments are provided, with the main difference being the composition of the glaze. The specific processes all adopt the above-described steps (not described in detail here):

[0081] Example 1:

[0082] Base glaze: by weight, the components are: 30 parts silicon dioxide, 15 parts boron trioxide, 4 parts aluminum oxide, 10 parts titanium dioxide, 2 parts cobalt oxide, 3 parts nickel oxide, 1 part copper oxide, 3 parts potassium oxide, 5 parts sodium oxide, 2 parts sodium fluorosilicate, 2 parts sodium nitrate, 2 parts nano zirconium oxide, and 1 part modified manganese oxide.

[0083] Transition layer: By mass, the components are: 35 parts silicon dioxide, 12 parts boron trioxide, 6 parts aluminum oxide, 15 parts titanium dioxide, 1 part cobalt oxide, 2 parts nickel oxide, 1 part copper oxide, 4 parts potassium oxide, 6 parts sodium oxide, 2 parts sodium fluorosilicate, 2 parts sodium nitrate, 3 parts nano zirconium oxide, and 2 parts modified silicon carbide.

[0084] Glaze: By weight, the components are: 40 parts silicon dioxide, 10 parts boron trioxide, 8 parts aluminum oxide, 20 parts titanium dioxide, 2 parts copper oxide, 5 parts potassium oxide, 8 parts sodium oxide, 1 part sodium fluorosilicate, 1 part sodium nitrate, 5 parts nano zirconium oxide, 3 parts silicon carbide, 0.2 parts borax, and 0.5 parts bentonite.

[0085] Example 2:

[0086] Base glaze: by weight, the components are: 32.5 parts silicon dioxide, 17.5 parts boron trioxide, 5 parts aluminum oxide, 12.5 parts titanium dioxide, 3 parts cobalt oxide, 4 parts nickel oxide, 2 parts copper oxide, 4.5 parts potassium oxide, 6.5 parts sodium oxide, 3 parts sodium fluorosilicate, 3.5 parts sodium nitrate, 2.5 parts nano zirconium oxide, and 1.5 parts modified manganese oxide.

[0087] Transition layer: By mass, the components are: 37.5 parts silicon dioxide, 15 parts boron trioxide, 7 parts aluminum oxide, 17.5 parts titanium dioxide, 1.5 parts cobalt oxide, 2.5 parts nickel oxide, 1.5 parts copper oxide, 5.5 parts potassium oxide, 7.5 parts sodium oxide, 2.5 parts sodium fluorosilicate, 3 parts sodium nitrate, 4 parts nano-zirconia, and 2.5 parts modified silicon carbide.

[0088] Glaze: By weight, the components are: 42.5 parts silicon dioxide, 12.5 parts boron trioxide, 9 parts aluminum oxide, 22.5 parts titanium dioxide, 2.5 parts copper oxide, 6.5 parts potassium oxide, 9 parts sodium oxide, 2 parts sodium fluorosilicate, 2 parts sodium nitrate, 6.5 parts nano zirconium oxide, 4 parts silicon carbide, 0.6 parts borax, and 0.75 parts bentonite.

[0089] Example 3:

[0090] Base glaze: by weight, the components are: 35 parts silicon dioxide, 20 parts boron trioxide, 6 parts aluminum oxide, 15 parts titanium dioxide, 4 parts cobalt oxide, 5 parts nickel oxide, 3 parts copper oxide, 6 parts potassium oxide, 8 parts sodium oxide, 4 parts sodium fluorosilicate, 5 parts sodium nitrate, 3 parts nano zirconium oxide, and 2 parts modified manganese oxide.

[0091] Transition layer: By mass, the components are: 40 parts silicon dioxide, 18 parts boron trioxide, 8 parts aluminum oxide, 20 parts titanium dioxide, 2 parts cobalt oxide, 3 parts nickel oxide, 2 parts copper oxide, 7 parts potassium oxide, 9 parts sodium oxide, 3 parts sodium fluorosilicate, 4 parts sodium nitrate, 5 parts nano zirconium oxide, and 3 parts modified silicon carbide.

[0092] Glaze: By weight, the components are: 45 parts silicon dioxide, 15 parts boron trioxide, 10 parts aluminum oxide, 25 parts titanium dioxide, 3 parts copper oxide, 8 parts potassium oxide, 10 parts sodium oxide, 3 parts sodium fluorosilicate, 3 parts sodium nitrate, 8 parts nano zirconium oxide, 5 parts silicon carbide, 1 part borax, and 1 part bentonite.

[0093] Experiment 1: Testing the uniformity of the inner wall ceramic layer thickness

[0094] The following are examples of settings:

[0095] The base material of the test specimen is Q235B carbon steel, commonly used in dryer cones. The dimensions of the test specimen are 150mm × 100mm × 3mm. The reference specimen is prepared using the industry's traditional enamel process, as detailed below:

[0096] Step 1: First, the test samples undergo uniform pretreatment: The steel plate surface is roughened using mechanical sandblasting with 80-mesh quartz sand at a pressure of 0.6 MPa. The entire surface of the sample is uniformly sanded to remove oxide scale, rust, oil, and rolling impurities, resulting in a uniformly rough, matte finish with a surface roughness of 40-60 μm. After sandblasting, high-pressure oil-free compressed air is used to blow away surface dust. Following this, chemical degreasing and pickling passivation are performed, involving alkaline degreasing solution, water rinsing, dilute acid rust removal, and pure water rinsing to thoroughly remove residual oil and oxides. Finally, the pretreated samples are placed in a constant-temperature drying oven at 120℃ for 30 minutes to completely remove surface moisture. After removal, they are placed in a dust-free, dry environment to cool and prepare for use, ensuring the substrate surface is clean, dry, and free of impurities.

[0097] Step 2: Select a special black enamel base glaze powder suitable for Q235B carbon steel, add pure water and special additives according to the standard ratio, stir thoroughly and let stand to defoam, and adjust to a base glaze slurry with a viscosity suitable for the dip-applying process; apply the coating using a manual dip-applying composite process, vertically immersing the cooled Q235B sample into the base glaze slurry, dipping at a uniform speed for 3-5 seconds, and then lifting it up steadily and vertically to avoid slurry dripping and accumulation. Then, use a special glaze application tool to manually touch up and repair areas where the glaze is easily thinned, such as the corners and edges of the sample, to ensure that the overall glaze layer of the sample is uniform, without missed areas or glaze accumulation; after coating, hang the sample in a dust-free, ventilated, and dry area for natural air drying for no less than 4 hours to allow the moisture in the base glaze slurry to fully evaporate until the base glaze layer is completely cured and the surface is dry and not sticky. The dry film thickness of the base glaze should be controlled at 0.2-0.3 mm.

[0098] Step 3: Using traditional enamel sintering process parameters, the sample, after being air-dried, is smoothly placed into the electric enamel sintering furnace and sintered using a segmented heating mode. First, the temperature is uniformly increased to 200℃ at a rate of 5℃ / min and held at this temperature for 15 minutes to completely evaporate any residual moisture inside the enamel layer. The temperature is then increased to the standard sintering temperature of 800℃ and held for 10 minutes to allow the base enamel to fully melt and impregnate the carbon steel substrate, forming a dense transition enamel layer with excellent adhesion. After sintering, the furnace heat source is turned off, and the sample is allowed to cool naturally to room temperature to avoid rapid cooling that could cause the enamel layer to crack or peel. After cooling, the surface of the base enamel is inspected to ensure there are no defects such as pinholes, cracks, peeling, or orange peel.

[0099] Step 4: After the base glaze sintering and cooling quality inspection is passed, the top enamel coating operation is carried out, still using the industry's traditional dip-coating process: Select a special medium-resistant and wear-resistant white transparent top glaze material for the drying equipment, prepare the top glaze slurry according to the process standard, stir thoroughly, let it stand to defoam, and set it aside; Use the same dip-coating process as the base glaze to uniformly dip the entire surface of the sample, and manually touch up and smooth key parts such as the edges and corners of the substrate and curved surfaces to ensure that the top glaze layer is of uniform thickness, smooth and flat, and completely covered without dead corners; After coating, the sample is placed in a dust-free and ventilated environment to air dry naturally for no less than 5 hours to ensure that the moisture in the top glaze layer evaporates completely, and the dry film thickness of the top glaze is controlled at 0.3-0.4mm to form a glaze layer structure that matches the gradient of the base glaze.

[0100] Step 5: After the surface glaze has dried in the shade, the sample is sent to the sintering furnace for a second high-temperature sintering, using the traditional mature sintering process parameters: the temperature is raised to 820℃ in stages and sintered at a constant temperature for 12 minutes to allow the surface glaze to fully melt and flow, and to fuse tightly with the underlying glaze layer to form a dense and complete enamel protective layer; after sintering, the sample is slowly cooled to room temperature in the furnace to prevent stress cracking of the glaze layer caused by rapid cooling; after cooling, the sample is trimmed as a whole, and the edges are lightly polished to remove glaze nodules and burrs, and the surface dust is cleaned.

[0101] The uniformity of the ceramic layer thickness of the inner wall of the cone obtained according to the processes of Examples 1-3 and the reference example was tested using GB / T7991.5-2014.

[0102] The method described in "Test Methods for Enameled Layers Part 5: Thickness Measurement by Electromagnetic Method" involves multi-point thickness measurement at multiple locations on a sample and calculation of the deviation in the enamel layer thickness. Specific data are as follows:

[0103]

[0104]

[0105] The experimental data in the two tables above show that:

[0106] The present invention significantly improves the overall thickness stability of the ceramic layer, eliminating the defect of extreme thickness: the average thickness of the ceramic layer in the traditional reference example is 0.76 mm. Due to the influence of gravity flow of glaze slurry, the upper region of the cone-shaped simulated sample is thinner, while the lower region has severe thickness accumulation, with a maximum thickness of 0.98 mm and a minimum thickness of only 0.62 mm, resulting in an overall thickness range as high as 0.36 mm and extremely high thickness distribution dispersion. In the embodiment of the present invention, the average thickness of the ceramic layer is increased to 0.81 mm, and the thickness of the ceramic layer is uniform throughout the substrate, with a maximum thickness of 0.85 mm and a minimum thickness of 0.78 mm, resulting in a thickness range of only 0.07 mm and a significant reduction in thickness fluctuation by 80.56%. Furthermore, the standard deviation of the thickness of the traditional process in the comparative example is 0.10 mm, with a thickness deviation of 13.30%. In the embodiment of the present invention, the standard deviation is reduced to 0.02 mm, and the thickness deviation is only 2.72%, a reduction of 79.55%, effectively solving the inherent defects of uneven thickness, local thin glaze leakage, and local thick glaze accumulation in the traditional process.

[0107] Experiment 2: Testing the Bond Strength of the Inner Wall Porcelain Layer

[0108] Using the above Examples 1-3 as a control, the following comparative examples were set up:

[0109] Comparative Example 1: Unlike Example 1, the modified manganese oxide in the base glaze was not modified, while the other components were the same;

[0110] Comparative Example 2: Unlike Example 2, the modified manganese oxide in the base glaze was not modified, while the other components were the same;

[0111] Comparative Example 3: Unlike Example 3, the modified manganese oxide in the base glaze was not modified, while the other components were the same;

[0112] Comparative Example 1: Unlike Example 1, the base glaze does not contain modified manganese oxide or manganese oxide, but the other components are the same;

[0113] Comparative Example 2: Unlike Example 2, the base glaze does not contain modified manganese oxide or manganese oxide, but the other components are the same;

[0114] Comparative Example 3: Unlike Example 3, the base glaze does not contain modified manganese oxide or manganese oxide, but the other components are the same;

[0115] Based on the above Examples 1-3, Comparative Examples 1-3 and Control Examples 1-3, relevant tests were conducted on the bonding strength performance of the porcelain layer. The testing was conducted in accordance with GB / T9286-1998, the industry standard for testing the adhesion of enamel layers in glass-lined equipment. The testing equipment was a digital display enamel coating adhesion tensile testing machine.

[0116] In this experiment, five parallel test points were used for each group of samples (point 1, point 2, point 3, point 4, and point 5). After removing outliers, the average bonding strength of each group and the overall mean were calculated. All data were measured in MPa and rounded to two decimal places. The specific test results are shown in the table below:

[0117]

[0118] The test results in the table above show that:

[0119] (1) The average bonding strength of blank control examples 1-3 was only 24.12 MPa. The overall strength was low and the data fluctuated greatly. The interface between the matrix and the base glaze relied only on cobalt and nickel oxides to form a simple spinel bond. The interface transition layer was sparse and had many micropores, resulting in poor adhesion stability.

[0120] (2) The bonding strength of Comparative Examples 1-3 with added unmodified manganese oxide was significantly improved, with an average strength increase of about 16.2%, proving that manganese oxide can effectively participate in the formation of spinel phase at the carbon steel interface, help improve coating adhesion, and is the core synergistic component of the base glaze adhesion system.

[0121] (3) Under the same dosage and process conditions, the bonding strength of each group of the modified manganese oxide examples is significantly better than that of the unmodified comparative examples 1-3, and the data stability is greatly improved, increasing by 18.8% compared with the unmodified system with the same dosage, effectively solving the performance problem of bonding strength.

[0122] Experiment 3: Testing the thermal shock resistance of the inner ceramic layer

[0123] Using the above Examples 1-3 as a control, the following comparative examples were set up:

[0124] Comparative Example 4: Unlike Example 1, the modified silicon carbide in the transition layer was not modified, while the other components remained the same;

[0125] Comparative Example 5: Unlike Example 2, the modified silicon carbide in the transition layer was not modified, while the other components were the same;

[0126] Comparative Example 6: Unlike Example 3, the modified silicon carbide in the transition layer was not modified, while the other components remained the same;

[0127] Comparative Example 4: Unlike Example 1, the transition layer does not contain modified silicon carbide or silicon carbide, but the other components are the same;

[0128] Comparative Example 5: Unlike Example 2, the transition layer does not contain modified silicon carbide or silicon carbide, but the other components are the same;

[0129] Comparative Example 6: Unlike Example 3, the transition layer does not contain modified silicon carbide or silicon carbide, but the other components are the same;

[0130] Based on Examples 1-3, Comparative Examples 4-6, and Control Examples 4-6 above, relevant tests were conducted on the thermal shock resistance of the ceramic layer. The test method in GB / T9757 standard was adopted. The sample was heated to 280°C and then immediately placed in cold water at 20°C for rapid cooling. This cycle was repeated 5 times, and the defects on the glaze surface were observed. The specific test results are shown in the table below:

[0131]

[0132] The test results in the table above show that:

[0133] (1) The silicon carbide-free ceramic layer of the control example showed microcracks in the second hot and cold cycle. After five cycles, the cracks became dense and the glaze layer fell off in large areas. The average residual bonding strength was only 12.80 MPa, which could not meet the requirements of the alternating temperature change working condition of the dryer cone.

[0134] (2) The physical filling of ordinary silicon carbide in the comparative example can improve the thermal shock resistance, postpone the first crack to the third cycle, and increase the average residual bond strength to 18.73 MPa. However, the problems of weak interface bonding and stress concentration have not been fundamentally solved. After 5 cycles, there are still obvious cracks and local detachment.

[0135] (3) The thermal shock resistance of the modified silicon carbide in the example is greatly improved. The titanium-lanthanum composite modified silicon carbide achieves gradient thermal expansion matching and crack deflection toughening through Si-O-Ti chemical bonding and rare earth stress relief. After 5 cycles of 280℃→20℃, there are no cracks or peeling on the glaze surface. The average residual bonding strength is as high as 30.27MPa, which is 136.5% higher than the control example and 61.6% higher than the unmodified control example.

[0136] Experiment 4: Testing the wear resistance of the inner wall ceramic layer

[0137] Based on Examples 1-3, Comparative Examples 4-6, and Control Examples 4-6 above, relevant tests were conducted on the thermal shock resistance of the ceramic layer. The test method was as follows: the abrasion test method in ASTM D4060 was used. The sample was subjected to an abrasion test for 30 minutes under a loading condition of 200N. After the test, the mass of the sample before and after wear (mg, retained to two decimal places) was measured, and the abrasion weight loss was calculated. The smaller the weight loss value, the better the abrasion resistance, density, and erosion resistance of the ceramic layer. The specific test results are shown in the table below:

[0138]

[0139] The test results in the table above show that:

[0140] (1) The transition layer of the control example has no hard wear-resistant skeleton phase, the overall structure of the ceramic layer is loose and the surface hardness is low. Under the continuous friction condition of 200N load, the average wear weight loss is as high as 5.86mg. The ceramic layer is very easy to generate abrasive wear and surface peeling, and cannot resist the long-term material scouring and wear of the dryer equipment, resulting in a short service life.

[0141] (2) After doping with unmodified silicon carbide, the wear resistance of the glaze can be slightly improved by relying on the high hardness of the powder itself, and the average weight loss is reduced to 3.19 mg, which is 45.56% lower than that of the control group. However, due to the inertness of the surface of unmodified silicon carbide, uneven dispersion, and micropores at the interface, the powder is easy to fall off and the skeleton support is poor. The improvement of wear resistance under large load is limited, and there is still a continuous wear defect under long-term scouring conditions.

[0142] (3) Modified silicon carbide can further improve wear resistance. Titanium-lanthanum composite modified silicon carbide can form a dense chemical bond network with the enamel glass phase, with uniform powder dispersion and no pore defects at the interface, thus constructing a continuous and stable hard wear-resistant skeleton. In the gradient test, the overall wear resistance of the example was much better than that of the comparative example and the control example, with a reduction of 76.62% compared with the control example system and a reduction of 57.05% compared with the comparative example system, showing a significant improvement in wear resistance.

[0143] The conclusions from Experiments 3 and 4 show that:

[0144] This invention relates to titanium-lanthanum composite modified silicon carbide, which achieves chemical bonding between silicon carbide and enamel system by constructing Si-O-Ti covalent bonds. By refining rare earth grains and matching thermal expansion gradient, the residual stress of the coating is greatly reduced, which not only solves the defect of thermal alternating cracking, but also greatly improves the material's resistance to erosion and wear.

[0145] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A process for enamel enamel coating on the inner wall of a dryer cone, characterized in that, Includes the following steps: S1. Surface treatment of the substrate: Mechanically remove rust from the inner wall of the cone, then roughen the inner wall to control the roughness within the range of 5-15μm. Then clean the inner wall to remove residual iron filings, dust, oil and other impurities. After cleaning, dry thoroughly to avoid secondary oxidation of the substrate surface. S2. Electrostatic dry spraying: The electrostatic dry spraying process is used to sequentially spray the base glaze, transition layer and top glaze on the inner wall of the treated cone. The dry film thickness of the base glaze, transition layer and top glaze are controlled differently according to different positions of the cone. The median particle size of the glaze powder of the base glaze, transition layer and top glaze is controlled in the range of 20-40μm, and the moisture content is strictly controlled below 0.1wt%. S3. Sintering process: The cone after spraying is placed in a controlled atmosphere electric furnace for sintering. During the heating stage of the sintering process, the heating rate in the furnace is strictly controlled within the range of 3-5℃ / min, the maximum sintering temperature is controlled between 780-800℃, the holding time is controlled between 10-15 minutes, and the cooling rate in the furnace is strictly controlled within the range of 2-4℃ / min. S4. Post-processing: After sintering, allow the enamel layer to cool naturally to room temperature and clean the surface.

2. The enamel enamel process for the inner wall of a dryer cone according to claim 1, characterized in that, The specific parameters of the electrostatic dry spraying process are as follows: the electrostatic voltage of the spray gun is stably controlled within the range of 70-90kV; the vertical distance between the spray gun and the inner wall of the cone is strictly controlled within the range of 10-25cm; and the rotation speed of the cone is matched with the moving speed of the spray gun.

3. The enamel enamel process for the inner wall of a dryer cone according to claim 2, characterized in that, The dry film thickness of the base glaze, transition layer, and top glaze is controlled as follows: In the stress concentration area of ​​the cone, the dry film thickness of the base glaze is controlled within the range of 100-150μm, the dry film thickness of the transition layer is controlled within the range of 50-80μm, and the dry film thickness of the top glaze is controlled within the range of 150-200μm. In the straight cylindrical section of the cone, the dry film thickness of the base glaze is controlled within the range of 80-120 μm, the dry film thickness of the transition layer is controlled within the range of 40-60 μm, and the dry film thickness of the top glaze is controlled within the range of 120-180 μm.

4. The enamel enamel process for the inner wall of a dryer cone according to claim 1, characterized in that, The base glaze, by weight, comprises the following components: 30-35 parts silicon dioxide, 15-20 parts boron trioxide, 4-6 parts aluminum oxide, 10-15 parts titanium dioxide, 2-4 parts cobalt oxide, 3-5 parts nickel oxide, 1-3 parts copper oxide, 3-6 parts potassium oxide, 5-8 parts sodium oxide, 2-4 parts sodium fluorosilicate, 2-5 parts sodium nitrate, 2-3 parts nano-zirconium oxide, and 1-2 parts modified manganese oxide.

5. The enamel enamel process for the inner wall of a dryer cone according to claim 4, characterized in that, The preparation process of the modified manganese oxide is as follows: Step 1: Solvent system preparation Mix anhydrous ethanol and deionized water according to the specified ratio, add glacial acetic acid to adjust the pH of the system to 4.5-5.0, stir at low speed for 5 minutes to form a uniform weakly acidic hydrolysis solvent system. Step 2: Silane hydrolysis activation The weighed KH-550 silane coupling agent was slowly added dropwise to the above solvent system. The mixture was kept at a constant temperature of 55℃ and a speed of 300r / min for 30min to allow the silane to be fully hydrolyzed to generate active silanol groups. Step 3: Rare earth doping modification Manganese oxide powder and nano-lanthanum oxide powder were added sequentially to the activated silane system, the stirring speed was increased to 500 r / min, and the mixture was stirred continuously at a constant temperature of 55-60℃ for 90-120 min. Step 4: Let it sit and mature. Stop stirring and let it stand at room temperature for 40 minutes to allow the modified groups to fully bond and solidify, eliminate free active groups on the powder surface, and improve the stability of the modified layer. Step 5: Post-processing The matured slurry is spread evenly on a tray with a thickness of 8-10 mm, and then placed in a constant temperature oven at 110-120℃ for 2.5-3 hours to completely remove the solvent and solidify the modified layer. After drying, it is pulverized using an air jet mill and passed through a 300-mesh standard sieve to finally obtain powdered modified manganese oxide, which is then sealed for later use.

6. The enamel enamel process for the inner wall of a dryer cone according to claim 1, characterized in that... The transition layer comprises, by weight, the following components: 35-40 parts silicon dioxide, 12-18 parts boron trioxide, 6-8 parts aluminum oxide, 15-20 parts titanium dioxide, 1-2 parts cobalt oxide, 2-3 parts nickel oxide, 1-2 parts copper oxide, 4-7 parts potassium oxide, 6-9 parts sodium oxide, 2-3 parts sodium fluorosilicate, 2-4 parts sodium nitrate, 3-5 parts nano-zirconium oxide, and 2-3 parts modified silicon carbide.

7. The enamel enamel process for the inner wall of a dryer cone according to claim 6, characterized in that... The preparation process of the modified silicon carbide is as follows: Step 1: Preparation of buffer hydrolysis solvent Mix anhydrous ethanol and deionized water according to the specified ratio, add glacial acetic acid to adjust the pH of the system to 4.2-4.8, stir at low speed at room temperature for 6 minutes to form a weakly acidic and stable buffer system. Step 2: Preparation of active titanium sol Tetrabutyl titanate was slowly added dropwise to a buffer solvent, and stirred at a constant temperature of 60℃ and a uniform speed of 350r / min for 25min to prepare a uniform and transparent active titanium sol. Step 3: Rare Earth Composite Modification Add silicon carbide powder and nano lanthanum oxide powder in sequence, increase the stirring speed to 550 r / min, and stir continuously at a constant temperature of 60-65℃ for 100-120 min; Step 4: Let it mature at room temperature Stop stirring and let it stand at room temperature in a sealed container for 50 minutes to allow the titanium sol to fully condense and solidify, stabilize the lanthanum oxide ions, completely eliminate free active groups on the powder surface, prevent the modified components from decomposing and falling off during high-temperature sintering, and ensure the high-temperature stability of the modified layer. Step 5: Drying, curing, crushing and sieving The modified slurry is spread into a thin layer of 7-9 mm and dried at a constant temperature of 115-125℃ for 3.0 h to completely remove the solvent and solidify the composite modified layer. After air jet milling, it is passed through an 800-mesh standard sieve to obtain powdered modified silicon carbide, which is then sealed and dried for storage.

8. The enamel enamel process for the inner wall of a dryer cone according to claim 1, characterized in that... The surface glaze, by weight, comprises the following components: 40-45 parts silicon dioxide, 10-15 parts boron trioxide, 8-10 parts aluminum oxide, 20-25 parts titanium dioxide, 2-3 parts copper oxide, 5-8 parts potassium oxide, 8-10 parts sodium oxide, 1-3 parts sodium fluorosilicate, 1-3 parts sodium nitrate, 5-8 parts nano zirconium oxide, 3-5 parts silicon carbide, 0.2-1 parts borax, and 0.5-1 parts bentonite.